The adventures of Captain Underpants : the first epic novel - Pilkey, Dav, 1966- (Pilkey, Dav, 1966- Adventures of Captain Underpants (Series), 2023)
When George and Harold hypnotize their principal into thinking that he is the superhero Captain Underpants, he leads them to the lair of the nefarious Dr. Diaper.